Selecting multimodal therapy for rhabdomyosarcoma. Issue 8 (August 2010) - Sultan, Iyad; Ferrari, Andrea
Rhabdomyosarcoma is a typical tumor of childhood, characterized by a high grade of malignancy, local invasiveness and a marked propensity to metastasize, but also a generally good response to chemotherapy and radiotherapy. Multimodal therapy is essential to cure rhabdomyosarcoma patients, but different uses of surgery, radiotherapy and chemotherapy, and their intensity, need to be selected and modulated to different patient risk groups. This article attempts to give an account of the current treatment options, the open and debated issues and the potential novel strategies for the near future.